2023
DOI: 10.3389/fendo.2023.1116482
|View full text |Cite
|
Sign up to set email alerts
|

Maternal androgen excess significantly impairs sexual behavior in male and female mouse offspring: Perspective for a biological origin of sexual dysfunction in PCOS

Abstract: IntroductionPolycystic ovary syndrome (PCOS) is the most common infertility disorder worldwide, typically characterised by high circulating androgen levels, oligo- or anovulation, and polycystic ovarian morphology. Sexual dysfunction, including decreased sexual desire and increased sexual dissatisfaction, is also reported by women with PCOS. The origins of these sexual difficulties remain largely unidentified. To investigate potential biological origins of sexual dysfunction in PCOS patients, we asked whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…For estradiol treatment, a 5-mm-long Silastic capsule (inner diameter: 1.57 mm; outer diameter: 2.41 mm) containing crystalline 17β-estradiol (E2758, Sigma-Aldrich, USA), diluted 1:1 with cholesterol (C8667, Sigma Aldrich), was inserted subcutaneously at the nape of the neck at the same time as ovariectomy, as previously described [ 44 ]. This is a routinely used method of exogenously elevating circulating E2 levels in mice [ 44-46 ]. Brain tissue from OVX mice was collected 3 weeks after ovariectomy and OVX + E2 mice 6 weeks after ovariectomy.…”
Section: Methodsmentioning
confidence: 99%
“…For estradiol treatment, a 5-mm-long Silastic capsule (inner diameter: 1.57 mm; outer diameter: 2.41 mm) containing crystalline 17β-estradiol (E2758, Sigma-Aldrich, USA), diluted 1:1 with cholesterol (C8667, Sigma Aldrich), was inserted subcutaneously at the nape of the neck at the same time as ovariectomy, as previously described [ 44 ]. This is a routinely used method of exogenously elevating circulating E2 levels in mice [ 44-46 ]. Brain tissue from OVX mice was collected 3 weeks after ovariectomy and OVX + E2 mice 6 weeks after ovariectomy.…”
Section: Methodsmentioning
confidence: 99%
“…However, two recent studies utilized robust preclinical animal models to investigate the underlying neural circuitry and found that female mice, prenatally exposed to either excess AMH (PAMH) or androgens (PNA), exhibit impaired sexual behavior and sexual partner preference throughout their reproductive age. 8 58 These studies shed light on the impact of prenatal hormone exposure on sexual function in PCOS-like animal models, providing insights into the potential neural mechanisms underlying sexual dysfunction in PCOS. Noteworthy, in the PAMH females, sexual dysfunction has been linked to a significant reduction in the number of neurons expressing neuronal nitric oxide synthase (nNOS) and progesterone receptor in the ventromedial nucleus of the hypothalamus (VMH).…”
Section: Prenatal Amh Exposure and Onset Of Sexual Dysfunctions In Pcosmentioning
confidence: 99%